ECO-EFFICIENCY AND DECOUPLING ANALYSIS OF AGRICULTURE SECTOR: A CASE STUDY OF PAKISTAN - Aslam, Muhammad; Khan, Afaq Ali; Ahmed, Naveed; Sanjrani, Riaz Deen (The journal of contemporary issues in business and government, 2022)
According to this study, the agriculture industry of Pakistan’s eco-efficiency trend and decoupling status between 2001 and 2018 will be examined. As a result, the agricultural sector’s impact on resources and the environment has been evaluated. Cropped area, fertilizer use, pesticide imports, and tractor output are proxies for resource use. Agricultural emissions are used as an environmental proxy. Farm output and emissions were estimated based on the World Bank and FAO data. However, there are some other indicators in the Pakistan Economic Survey 2019-20. Therefore, eco-efficiency and the Tapio Decoupling Elasticity Index, two novel approaches, were used in the analysis. Across the board, the results of the eco-efficiency studies show a rise in eco-efficiency. Despite this, the results of the decoupling research show that the indicators used in the study reveal scattered decoupling states throughout separate periods. Signs of severe decoupling, expensive negative decoupling, and weak decoupling are seen regularly. Increasing Pakistan’s agricultural eco-efficiency and decoupling may be possible via new technology, modern farming practices, and sound resource management. However, farmers’ education and awareness campaigns might be crucial to get the most out of available resources.